Analysis of the Impact of Land Cover Change in 2010-2024 on the Potential of Water Catchment Areas in the Arau Watershed - Muhammad Fajri; Iswandi U; Eri Barlian; Nurhasan Syah; Teguh Haria Aditia Putra (Postgraduate, University of Mataram, 2025)
The purpose of this research is to analyse the potential of water catchment areas and the impact of land cover change from 2010 to 2024. The research method used is quantitative research, with a descriptive approach. The analysis technique in this study uses the maximum likelihood analysis method, in analysing the classification of land cover in 2010 and 2024, and overlay analysis in analysing the potential of natural water catchment areas, land cover changes in 2010-2024, and the index of potential water catchment areas. Based on the results of the study, it can be concluded that the Batang Arau watershed has experienced a decrease in the area of potential water catchment areas, covering an area of 1057.80 hectares with a percentage of 5.94%, although it has increased the potential of water catchment areas covering an area of 238 hectares with a percentage of 1.34%, but the increase is not proportional to the decrease that has occurred. This decrease is due to land cover change from 2010-2024, with a reduction in forest area of 5.93%, wetland agriculture 2.49%, water bodies 0.02%, and grass 0.53%. This was accompanied by an increase in built-up areas of 7.94%, mixed gardens 0.73%, fields 0.10%, natural open land 0.002%, and shrubs 0.11%, So it can be concluded that the decrease in water catchment area is due to the reduction of forest area (natural vegetation), accompanied by an increase in built-up area